Performance of Garlic (Allium sativum L) Genotypes after Transplant Aman Rice Harvest under Zero Tillage Mulched Condition - Islam, M. R.; Uddin, M. K.; Mian, M. A. K.; Zaman, R.; Hossain, J. (International Journal of Applied Sciences and Biotechnology, 2015)
The selected garlic varieties/lines viz., BARI Roshun-1, BARI Roshun-2, GC0018, GC0024, GC0027, GC0034 and one local cultivar wereevaluated under zero tillage mulched condition to find out the suitable varieties/lines. There were significant differences among genotypes forall studied characters except number of leaves per plant. The advanced lines GC0018, GC0027 and GC0034 were graded as the highest bulbyield and it was more than 10 t/ha. But numerically the highest bulb yield (10.89 t/ha) was produced in GC0034 line while the local varietyproduced only 6.82 t/ha. GC0027 genotype was produce the longest plant (60.53 cm) and largest bulb diameter (3.94 cm), while local cultivarwas the minimum. Simple correlation analysis showed that there were positive and significant correlation among bulb yields with all theparameters except plant height and leaves per plant. Highest water use efficiency 44.63 kg ha-1 mm-1 was obtained from GC0034 line. In respectof monetary return GC0034 produced the maximum gross return (Tk. 653400/ha), gross margin (Tk. 515125/ha) and benefit cost ratio (4.73).The finding of this study could be useful for improving garlic production after transplant aman rice harvest under zero tillage mulched condition. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11216 Int J Appl Sci Biotechnol, Vol. 3(1): 26-30